2010
DOI: 10.1097/moo.0b013e32833bb16f
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in facial paralysis: advances and obstacles

Abstract: Management of facial paralysis remains an area of active investigation and innovation. The challenge to researchers and care providers will be to continue to explore and refine management strategies while maintaining rigorous and standardized means of evaluation and follow-up, such that outcomes may be determined and reported accurately and in a way that they can be transferred to other clinical practices. Further study of the role of growth factors and stem cells in facial nerve regeneration is critical, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Although experimental studies with growth factors, cell transplantation, and biomaterials have shown functional benefits, clinical translation remains a challenge . In the absence of effective cellular and molecular therapies, facial nerve injuries are managed acutely with dynamic surgical procedures, including nerve grafting, anastomosis, crossover, and muscle transfer to neurotized flaps .…”
mentioning
confidence: 99%
“…Although experimental studies with growth factors, cell transplantation, and biomaterials have shown functional benefits, clinical translation remains a challenge . In the absence of effective cellular and molecular therapies, facial nerve injuries are managed acutely with dynamic surgical procedures, including nerve grafting, anastomosis, crossover, and muscle transfer to neurotized flaps .…”
mentioning
confidence: 99%
“…Although facial nerve decompression is a suitable therapeutic option for facial nerve damage due to trauma or other causes of facial nerve compression, it requires that the anatomy of the facial nerve must be kept intact. There is also a certain time limit (within one month) in which it should be performed, otherwise the likelihood of successful treatment is reduced ( 2 ). Facial nerve transplantation, which involves connecting the two broken ends of the facial nerve via suture, or neural transplantation (connecting the facial nerve with a nerve taken from another area of the body), is a common method used for reconstructing the facial nerve ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…During this period, the motor end plate (nerve and muscle joint) may shrink, which leads to disuse atrophy. This is the main cause of permanent facial paralysis ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…7 Patients who undergo surgical procedures for advanced lateral skull base tumors that require facial nerve and adjacent musculature resection and cases of long-standing facial nerve paralysis often require multiple static and mimetic procedures to optimize cosmetic result and return of long-term function. 8,9 These can include the use of free muscle transfer, in conjunction with neural grafting, oculoplastic techniques, and static soft tissue tightening procedures.…”
Section: Introductionmentioning
confidence: 99%